2009
DOI: 10.1007/s10796-009-9194-8
|View full text |Cite
|
Sign up to set email alerts
|

Applying an organizational learning perspective to new technology deployment by technological gatekeepers: A theoretical model and key issues for future research

Abstract: Organizations often under-utilize expensive information technology (IT) enabled work processes that automate routines or processes that were previously carried out manually. One reason for this phenomenon may lie in the types of decisions made by technological gatekeepers, who are key individuals charged with deploying new technologies in organizations. From an organizational learning perspective, technological gatekeepers are more likely to perform successfully when they make appropriate decisions about explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 87 publications
0
5
0
1
Order By: Relevance
“…Similarly, the influence of expertise in technology use and/or adoption has been explored in many studies (Rau and Haerem, 2010; Goeke, 2006). In the case of technology use, Goeke found expertise to be much more salient than experience as a predictor of user perceptions of data warehouse ease‐of‐use, usefulness, and flexibility.…”
Section: Model Development and Relationships Formulationmentioning
confidence: 99%
“…Similarly, the influence of expertise in technology use and/or adoption has been explored in many studies (Rau and Haerem, 2010; Goeke, 2006). In the case of technology use, Goeke found expertise to be much more salient than experience as a predictor of user perceptions of data warehouse ease‐of‐use, usefulness, and flexibility.…”
Section: Model Development and Relationships Formulationmentioning
confidence: 99%
“…As TI vêm se tornando, cada vez mais, parte integrante das ferramentas de gestão das organizações, em razão da dependência cada vez maior de informação e conhecimento [8] [9]. Elas aceleram a velocidade com que a informação é adquirida e disseminada por toda a empresa e ajudam a assegurar que cada membro da empresa está atualizado, no que diz respeito a informações relevantes do mercado.…”
Section: A Competências Em Tecnologias Da Informaçãounclassified
“…In addition, Nah & Delgado (2006) also stated that the commitment of high-ranking supervisors is one of key success factors of participation in an Enterprise resource planning (ERP) system. Rau & Haerem (2010) presented a model based on the basic technology acceptance model (TAM) to examine the organizational learning perspective with regard to the deployment of new technology by technological gatekeepers. Choi et al (2007) suggested an e-Learning success model for ERP training based on the theory of flow, and found that flow experience had a critical role in their research model, having direct and indirect impacts on learning outcomes.…”
Section: Organizationmentioning
confidence: 99%